Discourse of Family Well-Being and the Value of Work at RPTRA’s Testimonial Videos - Sunar Wibowo; Rustono Farady Marta; Hana Panggabean (Jurnal Masyarakat dan Budaya, 2019)
Well being is one of the global SDGs (Sustainable Development Goals) movement in which Indonesian Government formally join. Integrated child friendly public spaces (Ruang Publik Terpadu Ramah Anak or abbreviated as RPTRA â€“ in Indonesian), are built for improving cities to become Child Friendly Cities, which actually serve as a component for achieving this well-being SDG. This study aims  to show how RPTRA staff creatively communicate to public by uploading testimonial videos on YouTube,  which is intended to show how RPTRAâ€™s existence is perceived by its surrounding community. Analyzing a sample of such videos using the Faircloughâ€™s critical discourse analysis, it was found that RPTRAs provide real benefits  not only to children, but also to all family members, contributing to family well being. To put it in the context of RPTRA employment fenomena, the testimonial video also reveals the job meaningfulness as perceived by the RPTRA staff.